The Effect of Good Corporate Governance on Financial Distress - Fadila Angraini (Research of Finance and Banking, 2023)
This research aims to examine the influence of Good Corporate Governance as proxied by the Board of Directors, Independent Commissioners, Audit Committee, and Institutional Ownership on Financial Distress partially or simultaneously. The research method used is quantitative and uses secondary data, namely service companies, one of which is the transportation sector listed on the Indonesia Stock Exchange. The sample used was 7 issuers, and the results were obtained using a purposive sampling method. The analytical method used is multiple linear regression analysis techniques with Spss Version 25 software. This research shows that overall, the size of the Board of Directors, Independent Commissioners, Audit Committee, and Institutional Ownership variables partially or simultaneously influence Financial Distress. This research can guide companies to understand the importance of mitigating financial risks by implementing strong GCG principles. It can include debt management, monitoring financial policies, and making wise investment decisions. The implications of this research can guide investors and creditors in assessing the risks and return potential associated with well-managed companies in terms of governance. The implication is that external stakeholders can use this information to support their investment decisions.